SOME OBSERVATIONSO N THE PERFORMANCE OF IO.S m MID .. WATER TRAWl OPERATED OFF VERA VAl - SIVAN, T M; DESHPANDE, S D; RAMARAO, S V.S (Fishery Technology, 2025)
The communication presents the results of fishing trials conducted off Veraval with a 10.5 m four-seam unequal paneled mid-water trawl with vertically curved otter boards. The design and structural details of net and otter boards are described in detail. Particulars such as the fish caught during experimentation, horizontal spread of the net as well as towing resistance offered in action are also incorporated.